Preventive effect of the bark of Passiflora edulis on obesity-related disorders and oxidative stress in db/db mice - Panelli, Marielle Fernanda [UNESP]; Garcia, Jéssica Leite [UNESP]; de Souza, Sérgio Luiz Borges [UNESP]; Costa, Mariane Róvero [UNESP]; Ferron, Artur Junio Togneri [UNESP]; Gregolin, Cristina Schmitt [UNESP]; Minatel, Igor Otávio [UNESP]; Ferraz, Ana Paula Costa Rodrigues [UNESP]; Pierine, Damiana Tortolero [UNESP]; Francisqueti- Ferron, Fabiane Valentini [UNESP]; Corrêa, Camila Renata [UNESP] (Springer Nature, 2019)
Purpose: To verify if the bark of Passiflora edulis prevents obesity-related disorders and oxidative stress in db/db mice. Methods: Obese male db/db mice (n = 14 animals) were randomly divided into two groups to receive standard chow and water (obese, n = 7 (OB)) or standard chow with bark of Passiflora edulis (BPe) (obese + BPe, n = 7 (OB + BPe)) for 16 weeks. The evaluated parameters in animals included food and caloric intake, body weight, total body fat and fat deposits, serum glucose, triglycerides, and total cholesterol. Malondialdehyde (MDA) and antioxidant capacity were evaluated in serum and organs (adipose tissue, kidney, liver, and heart). All groups were compared by Student t test, with p < 0.05. Results: The results showed the benefits from BPe by preventing abdominal fat deposition and by reducing the total cholesterol. Moreover, the compound increased the antioxidant capacity from the organs analyzed and reduced the MDA levels in the liver. Conclusion: It is possible to conclude that the consumption of the BPe prevents obesity-related disorders and oxidative stress in db/db mice.
Keywords: Db/db mice; Obesity; Passion fruit